Dapagliflozin and Acute Kidney Injury Following Cardiac Surgery - Maartina J. P. Oosterom-Eijmael; Abraham H. Hulst; Nelson P. Monteiro de Oliveira; Ed D. Niesten; Nicobert E. Wietsma; Bastiaan M. Gerritse; Thierry V. Scohy; Thijs C. D. Rettig; Ferdinand T. F. Snellen; Magiel F. Voogd; Marc B. Godfried; Rients N. de Boer; et al. (JAMA, 2026)
Importance Two percent to 50% of patients undergoing elective cardiac surgery experience acute kidney injury (AKI) postoperatively. Medications to prevent AKI after elective cardiac surgery have not been identified. Objective In patients undergoing elective cardiac surgery, to evaluate whether initiating dapagliflozin 1 day prior to surgery reduces the incidence of AKI at 7 days after cardiac surgery, compared with placebo. Design, Setting, and Participants Multicenter, double-blind, placebo-controlled randomized clinical trial conducted at 2 academic medical centers and 5 nonacademic hospitals in the Netherlands. Eligible participants were adults undergoing elective cardiac surgery. Enrollment occurred between June 8, 2023, and January 27, 2025. Final follow-up occurred May 16, 2025. Intervention Patients were randomized 1:1 to receive either dapagliflozin (10 mg orally; n = 392) or placebo once daily (n = 392), beginning on the day before surgery and continuing through the second postoperative day (total of 4 doses). Main Outcome and Measure The primary outcome was the between-group difference in AKI (defined as an increase in serum creatinine level by at least 0.3 mg/dL [26.5 µmol/L] within 48 hours after surgery, a 1.5-fold creatinine increase within 7 days of surgery, or urine output less than 0.5 mL/kg/h for 6 to 12 hours according to Kidney Disease: Improving Global Outcomes criteria) during the first 7 postoperative days. Results Of 784 participants enrolled, 778 (99%) completed follow-up testing (median age, 68 [61-74] years; 76% male; 97% White; median body mass index, 27 [IQR, 25-30]; and median estimated glomerular filtration rate, 80 [IQR, 67-89] mL/min/1.73 m 2 ). Compared with placebo, dapagliflozin reduced the incidence of AKI (28% vs 52%; relative risk, 0.54 [95% CI, 0.45-0.65]; P < .001) over 7-day follow-up after surgery. Atrial fibrillation and reoperation were the most frequent adverse events. The incidence of atrial fibrillation was 45% (176/392) in the dapagliflozin group vs 45% (176/392) in the placebo group, and the incidence of reoperation was 11% (43/392) vs 10% (39/392), respectively. Conclusions and Relevance In patients undergoing elective cardiac surgery, 4 doses of dapagliflozin, beginning the day before surgery, reduced the incidence of AKI during the 7-day postoperative period. Trial Registration ClinicalTrials.gov Identifier: NCT05590143